Analysis Effectiveness Feed Warehouse Automation Cattle Using Smart Sensors and Robotics - Komarudin Komarudin (Politeknik Siber Cerdika Internasional, 2025)
Improvement efficiency operations in the sector farm be one of focus main in face challenge productivity and sustainability . Research This aim For analyze effectiveness system automation warehouse feed livestock that integrates smart sensors and robotics , with studies cases in two warehouse scale middle school in Indonesia. Approach qualitative used with method studies case through interview in-depth , observation field , and analysis document system automation . Research results show that automation capable lower time distribution up to 44%, reducing need power Work by 50%, and increase accuracy recording stock until more from 95%. Users system show adaptation positive after training and systems proven support transparency as well as safety work . Implications from study This leading to potential replication system For farm scale more wide and become base for development technology logistics farm smart in Indonesia.